Fabrication of dimensional hydrophilic TiO2 nanostructured surfaces by hydrothermal method. (2021) - Manisha; Kumar, Vijay; Kumar Sharma, Deepak
Abstract: The hydrophilic dimensional Titanium dioxide (TiO2 ) nanostructured surface has been fabricated using the hydrothermal method. In this study, fluorinated tin oxide coated (FTO) glass is used as a transparent conductive substrate for the growth of TiO2 nanostars. FTO has the same crystal structure as TiO2 such that FTO promotes epitaxial nucleation and rutile evolution. The morphological characterization is done by Field Emission Scanning Electron Microscopy (FESEM) and X-ray diffraction (XRD). The FESEM shows that the stars like morphology of the TiO2 nanorods are obtained. The X-ray spectra reveal a tetragonal structure, which matches very well with the Joint Committee on Powder Diffraction Standards (JCPDS) data of rutile TiO2 with an average crystallite size of TiO2 nanostars are of 18.3 nm. The contact angles of hydrophilic TiO2 nanostructured surfaces after UV-light irradiation for 30 min were 41 ± 5° and 48 ± 5° respectively. The objective of our present work uses an FTO glass substrate with a transparent conductive growth of TiO2 nanostars hydrophilic in nature which has its applications in self-cleaning, anti-fouling, and antifungal processes.